Desmoplasia and chemoresistance in pancreatic cancer - Schober, Marvin; Jesenofsky, Ralf; Faißner, Ralf; Weidenauer, Cornelius; Hagmann, Wolfgang; Michl, Patrick; Heuchel, Rainer L.; Haas, Stephan; Löhr, J.-Matthias (Cancers, 2014)
pancreatic cancer, desmoplasia, drug resistance, SFM-DR, CAM-DR, de novo resistance, cancer stem cells, matrix, future therapies